EFFISIENSI TRAY TEORITIS DE-ETHANIZER COLUMN DI PT. TITIS SAMPURNA LPG PLANT LIMAU TIMUR - Aliyah Shahab; Achmad Faisal (Politeknik Negeri Sriwijaya, 2022)
Distillation is the most used separation and purification method in the chemical industry. The main products at PT. Titis Sampurna is an LPG. Before becoming an LPG product, the ethane component must be separated first. De-Ethanizer Column is the place where the separation of ethane content is still contained in the feed. During running time, the flow rate entering the DeEthanizer Column has decreased significantly. So it is necessary to calculate the minimum Tray in order to get optimal results, as well as to understand the function and workings of the DeEthanizer Column Based on the calculation results, the number of theoretical Trays obtained was 14 Trays. So the De-Ethanizer Column operated well in separating the ethane content which was still contained in the feed Keywords: Distillation, De-Ethanizer Column, Theoretical Tray